THE PROBLEMS REFORMATION OF UKRAINIAN RAILWAY TRANSPORT - Kopytko, V. I. (Science and Transport Progress, 2007)
An the article some problems of reformation of the railway transport in Ukraine, taking into consideration evaluations criteria of effectiveness and development of transport, state of production-technical basis and technological level of transportation are considered. Measures as regards to improvement service in the railway transport are proposed, the necessity of the transport market analysis taking into account the fact that «Ukrzaliznytsya» is one of the branches of natural monopoly is proved. Introduction of the informational resource as a component of getting eventual result will permit to complete structural reform of the railway transport.